D. x=<span>−<span>4 Why? </span></span>Let's solve your equation step-by-step. <span><span>2<span>(<span>x−7</span>)</span></span>=<span><span>10x</span>+18 </span></span>Simplify both sides of the equation. <span><span>2<span>(<span>x−7</span>)</span></span>=<span><span>10x</span>+18 </span></span><span>Simplify: </span><span><span><span>2x</span>−14</span>=<span><span>10x</span>+18 </span></span>Subtract 10x from both sides. <span><span><span><span>2x</span>−14</span>−<span>10x</span></span>=<span><span><span>10x</span>+18</span>−<span>10x </span></span></span><span><span><span>−<span>8x</span></span>−14</span>=18 </span>Add 14 to both sides. <span><span><span><span>−<span>8x</span></span>−14</span>+14</span>=<span>18+14 </span></span><span><span>−<span>8x</span></span>=32 </span>Divide both sides by -8. <span><span><span>−<span>8x</span></span><span>−8</span></span>=<span>32<span>−8 </span></span></span><span>D. x=<span>−<span>4</span></span></span>